2016
DOI: 10.1186/s12889-016-3381-6
|View full text |Cite
|
Sign up to set email alerts
|

Active children through incentive vouchers – evaluation (ACTIVE): a mixed-method feasibility study

Abstract: BackgroundAdolescents face many barriers to physical activity, demonstrated by the decline in physical activity levels in teenage populations. This study aimed to assess the feasibility of overcoming such barriers via the implementation of an activity-promoting voucher scheme to teenagers in deprived areas.MethodsAll Year 9 pupils (n = 115; 13.3 ± 0.48 years; 51 % boys) from one secondary school in Wales (UK) participated. Participants received £25 of activity vouchers every month for six months for physical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(83 citation statements)
references
References 31 publications
6
77
0
Order By: Relevance
“…9 Teenagers report the main barrier to meeting PA recommendations is accessibility to PA opportunities. 4,10,11 Accessibility is affected by cost, lack of local facilities, and motivation among teenagers, 10,12 especially those from disadvantaged backgrounds. 13 Self-determination theory (SDT) 14 has emerged as a popular framework for examining motivation and PA 15 as it differentiates between controlled motivation (e.g., regulated by external pressure or guilt) and autonomous motivation (e.g., regulated by enjoyment).…”
mentioning
confidence: 99%
“…9 Teenagers report the main barrier to meeting PA recommendations is accessibility to PA opportunities. 4,10,11 Accessibility is affected by cost, lack of local facilities, and motivation among teenagers, 10,12 especially those from disadvantaged backgrounds. 13 Self-determination theory (SDT) 14 has emerged as a popular framework for examining motivation and PA 15 as it differentiates between controlled motivation (e.g., regulated by external pressure or guilt) and autonomous motivation (e.g., regulated by enjoyment).…”
mentioning
confidence: 99%
“…The project encourages teenagers to access existing provisions or generate their own in order to tackle accessibility issues and create the opportunity to participate in desired activities [15]. Evidence has shown that empowering teenagers to make their own choices over which activity they engage in, the location where they engage, and the people they participate with, can improve activity levels [17].…”
Section: Introductionmentioning
confidence: 99%
“…The trial concluded that the addition of a financial incentive was effective in increasing physical activity levels. Christian et al 30 also sought to explore the feasibility of using financial incentives to increase physical activity levels in a teenage population (13.3 ± 0.43 years). The intervention involved provision of £25 of vouchers (five vouchers in increments of £5) per month for 6 months.…”
Section: Financial Incentivesmentioning
confidence: 99%